2019
DOI: 10.1002/pon.4983
|View full text |Cite
|
Sign up to set email alerts
|

Creating a teachable moment in community pharmacy for men with prostate cancer: A qualitative study of lifestyle changes

Abstract: Objective It is well established that exercise and lifestyle behaviours improve men's health outcomes from prostate cancer. With 3.8 million men living with the disease worldwide, the challenge is creating accessible intervention approaches that lead to sustainable lifestyle changes. We carried out a phase II feasibility study of a lifestyle intervention delivered by nine community pharmacies in the United Kingdom to inform a larger efficacy study. Qualitative interviews explored how men experienced the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Men with prostate cancer in these studies also sometimes reported that they required help from others to be motivated, that ongoing social support in planning and engaging with PA is a facilitator, that they needed physical concerns to be addressed during PA engagement, that their PA programme needed to be individualised, and that they valued objective feedback as a motivator . These are all areas that, according to the reviewed studies, can come under the remit of the exercise physiotherapist/specialist.…”
Section: Qualitative Synthesis Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Men with prostate cancer in these studies also sometimes reported that they required help from others to be motivated, that ongoing social support in planning and engaging with PA is a facilitator, that they needed physical concerns to be addressed during PA engagement, that their PA programme needed to be individualised, and that they valued objective feedback as a motivator . These are all areas that, according to the reviewed studies, can come under the remit of the exercise physiotherapist/specialist.…”
Section: Qualitative Synthesis Resultsmentioning
confidence: 99%
“…Many of the included qualitative studies were of good quality, fulfilling most JBI appraisal criteria, bar that which is commonly not reported (eg, statements locating the researchers culturally/theoretically) (see Appendix S1). Methodological issues amongst the other studies and issues relating to congruity of research question, methods, and interpretation were not representing participants voices adequately, Some appraisal criteria were unfulfilled by default because of an apparent lack of detail in reporting, a common occurrence being reports not addressing the influence of the researcher on the research (and vice versa) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,[30][31][32]35,36 However, research shows that individuals with prostate cancer have a high willingness to be active and that a window of opportunity for behaviour change or "teachable moment" may exist. 28,[37][38][39][40] Considering that the majority of individuals with prostate cancer do not currently achieve the recommended weekly exercise levels, new efficacious approaches supporting exercise adoption and adherence are needed.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%